Effects of plant growth regulators on indirect somatic embryogenesis in kenaf (hibiscus cannabinus ) (2006)
To develop protocols for regeneration of kenaf via indirect somatic embryogenesis, hypocotyl and cotyledon explants of two genotypes were cultured at different 2,4- dichlorophenoxyacetic acid and kinetin concentrations. The highest callus yields were obtained in medium containing both 0.5mg of kinetin and 0.1mg of 2, 4-dichlorophenoxyacetic acid per litre of medium. The calli were further cultured in twelve different media containing different plant growth regulators to induce somatic embryogenesis. Friable calli were mostly produced in one genotype (Ifeken400) and non-friable in the other (Ifeken400). Among the plant growth regulator regimes, media containing 3.0mg/I of kinetin and that containing 1.5mg/l each of kinetin and NAA did not support production of globular embryos in both varieties. The friable and non- friable caili were most responsive to kinetin and NAA respectively in terms of formation of torpedo embryos. The most advanced walking stick embryos were produced only in Ifeken400 in 1.5mg/l NAA. The importance of genotype and callus type in successful regeneration of kenaf by indirect somatic embryogenesis is discussed. Research is ongoing to achieve whole plantlet regeneration.